Phantom Pain in a Patient with Brachial Plexus Avulsion Injury. Issue 4 (2nd April 2015) - Shankar, Hariharan; Hansen, Jared; Thomas, Kisha
Abstract: Objective: Phantom limb pain is a painful sensation perceived in the absent limb following surgical or traumatic amputation. Phantom limb sensations, which are nonpainful, occur in nearly all amputees. Deafferentation can also produce similar symptoms. Here we report the presence of phantom pain in a deafferented limb. Design: Case report. Setting: Hospital-based outpatient clinic. Patient: A 65-year-old man was referred to the pain clinic for management of upper extremity pain secondary to brachial plexus avulsion (BPA) following a motor vehicle accident. Initially he noticed a feeling of growing and shrinking of his arm. Following this, the pain started gradually from his elbow extending to his fingertips covering all dermatomes. He described the pain as continuous, severe, and sharp. He also described the arm as being separate from his existing insensate arm and felt as though the fist was closed with the thumb pointing out. On physical examination, he had no sensation to fine touch or pressure below the elbow. There were no consistent areas of allodynia. He had diffuse muscle wasting in all the muscle groups of his left upper extremity, besides winging of the scapula. Electrodiagnostic studies showed a left brachial plexopathy consistent with multilevel nerve root avulsion sparing the dorsal rami. Conclusion: This is a report of phantom limb sensations and phantom pain following BPA in an intact but flaccid and insensate limb.